A273 COMPLIANCE WITH FIT SCREENING IN A CANADIAN PROVINCIAL COLON CANCER SCREENING PROGRAM LEADS TO GREATER LIKELIHOOD OF AN EARLY STAGE AT DIAGNOSIS. (15th March 2019) - MacIntosh, D
Abstract: Background: Since 2009, a province-wide colorectal cancer (CRC) screening program has been underway in Nova Scotia. Fecal immunochemical tests (FIT) have been mailed to each NS resident age 50–74 every two years. Subjects with a positive FIT result undergo colonoscopy. Currently uptake with FIT is approximately 30%. Aims: We decided to determine if there was a difference in the stage at diagnosis between FIT compliant and non-compliant Nova Scotians diagnosed with CRC since 2009. Methods: The authors identified ICD-O-3 codes for cancer sites, histologies and behaviour for cancers that can be detected with FIT. The appropriate cancers were abstracted from the Nova Scotia Cancer Registry (NSCR) for colorectal cancers diagnosed between 2001 and 2016. Patients diagnosed with cancer during or after 2009 were matched with the Nova Scotia Colon Cancer Prevention Program (NSCCPP) Cancer Care Application Screening Platform and Event Relationships (CCASPER) database to determine FIT screening compliance. Cancers were defined as "screen detected" if the patient had a positive FIT test result between 30 months and 22 days prior to the diagnosis date. All others were considered non-compliant with FIT screening. The distribution of the stage at diagnosis for cancers diagnosed prior to the onset of NS screening program (2009) was determined using NSCR data. Subsequently, the stage distribution for cancers diagnosed after the start of screening program for both non-participants and participants of the screening program was also determined from the NSCR. Results: When diagnosed with CRC before the onset of programmatic screening (2001–09), approximately 45% of Nova Scotians were discovered at a late stage (3–4). Subsequently with the introduction of FIT screening, the proportion of late stage at diagnosis has not changed if subjects were noncompliant (49%). However, in subjects diagnosed in the setting of positive FIT, the proportion of late stage at diagnosis has been markedly reduced (27%). More than half (54%) of compliant subjects were stage 0/1 at diagnosis. Conclusions: Compliance with a FIT screening program results in a clinically significant greater likelihood of earlier stage of CRC at diagnosis. The NSCCPP needs to improve uptake of FIT screening in Nova Scotia. Funding Agencies: None